Faktor-Faktor Yang Mempengaruhi Pengungkapan Intellectual Capital (Studi Empiris Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2012) - Andari, Isti Kusuma; , Dr. Zulfikar, SE, M.Si (2015)
Globalization has changed the business strategy which was labor based business into knowledge based business. Intellectual capital can be an important factor for companies to improve competitiveness.The study aimed to analyze the influence of firm performance, length of listing on IDX, firm size, growth rate, firm age, leverage, proportion of independent commissioner, and ownership concentration on intellectual capital disclosure. The population of this study are all banking companies listed in Indonesia Stock Exchange in 2011-2012. The sample was selected using purposive sampling method and obtained 31 samples of the banking company.Data sources obtained by IDX website, each company website, and ICMD. The data analysis methods used in this study is multiple linear regression analysis. This research has passed the test of classical assumptions which include normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. The results of this study showed that firm size, firm age, and leverage had significant influences on intellectual capital disclosure. Meanwhile, firm performance, length of listing on IDX, growth rate, proportion of independent commissioner, and ownership concentration had no significant influences on intellectual capital disclusure